Pengaruh Hambatan Samping Terhadap Kinerja Ruas Jalan Dr. Ratulangi Kota Makassar (Studi Kasus: Ruas Jalan Depan Toko New Agung) - Ariel Risa Parrung; Jonie Tanijaya; Louise Elizabeth Radjawane (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
A good transportation system provides maximum performance and service to the community. Traffic performance that is less than optimal will cause congestion that can disrupt people's daily activities. One of the factors that can reduce the level of performance and transportation services is the increase in vehicle volume and side friction factors on roads. Along the road Dr. Ratulangi has shops, shopping centers, restaurants and offices so that the area is dense with community activities, this creates traffic problems that cause congestion. This study aims to determine the traffic flow and the impact of side barriers on the degree of saturation on Jalan Dr. Ratulangi in front of the New Agung Store, Makassar City. In processing the data, the 2014 Indonesian Road Capacity Guidelines (PKJI) were used, the research data taken were primary data obtained from survey results at the location in the form of traffic volume data, side barriers, vehicle speed and road geometry as well as secondary data, namely the population of Makassar City. The research results from 3 days of observation obtained the largest volume of traffic flow on Monday where the south direction is 1807.4 cur/hour and the north direction is 1850.2 cur/hour. The highest side friction is on Monday with a total of two directions during the clock flow the average peak is 1364.2 events/hour and the average degree of saturation is in the south direction is 0.709 and the north direction is 0.726.